Does Tax Planning Affect Analysts' Forecast Accuracy? - Francis, Jere R.; Neuman, Stevanie S.; Newton, Nathan J. (Contemporary Accounting Research, 2019)
ABSTRACT We investigate whether firms' tax planning affects the accuracy of analysts' forecasts. Tax planning can exacerbate the complexity of firms' operations through strategic choices to exploit tax laws. Because of its effect on firms' operations, tax planning can influence analysts' efforts to understand and forecast earnings. Specifically, if the additional complexity arising from tax planning makes firm attributes less representative of expected earnings, analysts may issue less accurate forecasts. Using auditor‐provided tax services (APTS) as a measure of tax planning, we find that, as firms spend more on tax planning, the accuracy of analysts' forecasts of both earnings per share and tax expense declines. We also document that firms with higher levels of APTS have greater year‐to‐year volatility in, and lower persistence of, effective tax rates and earnings. Our results suggest that increased firm complexity, due to greater tax planning, makes earnings and tax expense more difficult to forecast and that analysts do not properly adjust for these effects. Thus, when deciding to engage in tax planning, firms appear to make trade‐offs between potential tax savings and negative effects on earnings properties and analysts' forecasts.